About the effective organization of independent education; The 8th Korea-Russia International Symposium on Science and Technology (KORUS 2004), June 26 - July 3, 2004, Tomsk, Russia; Vol. 3 - Tarbokova T. V. Tatyana Vasilievna (2004, 2004)
Title screen